PENERAPAN K-MODES DALAM KLASTERISASI KABUPATEN/KOTA DI JAWA BARAT BERDASARKAN INDIKATOR INFRASTRUKTUR - Rahman, Abd.; Anadra, Rahmi; Fitrianto , Anwar; Erfiani, Erfiani; Dwi Jumansyah, L.M. Risman (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Clustering is a statistical method used to group data based on certain similar characteristics, particularly in the context of complex and diverse data. This study aims to cluster districts/cities in West Java Province based on infrastructure indicators, namely access to clean water, sanitation, electricity, and energy, using the K-Modes clustering method. The data used is categorical data sourced from SUSENAS West Java 2023. The cluster analysis resulted in four distinct clusters, each representing significant differences in infrastructure characteristics across regions. The first cluster consists of 8 regions, the second cluster includes 7 regions, the third cluster consists of 1 region, and the fourth cluster contains 11 regions. These characteristic differences among clusters indicate infrastructure disparities that need to be addressed in planning more equitable development to improve the quality of life of people in West Java